Analysis Of The Meaning And Function Of Huler Wair Ceremony In Waiara Village, Kewapante District Sikka Regency - Yuliovi, Agustina; Nasa, Rikardus; M. K. Naro, Antonius (Journal of Social Science and Humanities Research, 2023)
This research aims to describe the meaning of “huler wair “ceremony in Waiara village Kewapamte ditrict, Sikka regency and describe the function of “huler wair” ceremony in Waiara village Kewapante district, Sikka regency.The formulation of the problem in this study (1) what is the meaning of “ huler wair” ceremony in waiara village, kewapante disttict, sikka regency? (2) what is the function of “huler wair” ceremony in waiara village, kewapante district, sikka regency? In this study using qualitative methods and data collection in this research is done by interviews, and documentation. The data that has been collected is analyzed descriptively, namely (1) collecting data (2) selecting data (3) reviewing data (4) drawing conclusionsin the form of functions and meanings at the huler wair ceremonyanalysis in the discussion of this research, it is concluded that the meaning of the huler wair ceremony in Waiara village, the function of the huler wair ceremony in Waiara village and the function of idioms as a function of hope and advice.